Hysteretic behavior of improved Pall-typed frictional dampers - Wu, B; Zhang, J; Williams, M; Ou, J (2005)
A new type of Pall frictional damper (PFD) with a simple configuration has been developed. The construction details, operation and damper force of the improved PFD (IPFD) are compared with those of the original PFD (OPFD). Force analyses using the virtual work principle show that the resisting forces generated by the two dampers are identical with identical frictional forces. Hence the IPFD replicates the mechanical properties of the OPFD, but offers some advantages in terms of ease of manufacture and assembly. The hysteretic behavior of PFDs (either IPFDs or OPFDs) is studied using a rigorous numerical method considering geometric nonlinearity. The numerical results show that the tension force of the brace does not remain constant as usually assumed but increases significantly when the PFD is sliding. The results are compared with and verified by finite element analyses using the commercially available ANSYS program. A simplified analysis is then performed to give a clearer insight into the source of the geometric nonlinearity which causes the increase of brace force. Finally, a validation experiment with IPFDs is carried out, which confirms the behavior identified in the preceding analyses. © 2005 Elsevier Ltd. All rights reserved.